Submillisievert Multiphasic Coronary Computed Tomography Angiography for Pediatric Patients With Congenital Heart Diseases. (February 2019) - Le Roy, Julien; Vernhet Kovacsik, Hélène; Zarqane, Hamid; Vincenti, Marie; Abassi, Hamouda; Lavastre, Kathleen; Mura, Thibault; Lacampagne, Alain; Amedro, Pascal
Abstract : Background: The use of coronary computed tomography (CT) angiography in children with coronary artery anomalies is increasing. However, it remains technically demanding and the need to adapt acquisition parameters to a patient's cardiac characteristics has not yet been addressed. The aim of the study was to prospectively assess the feasibility of personalized multiphasic coronary CT angiography for pediatric patients. Methods: Fifty pediatric patients (mean age 6.1±4.9 years) with coronary artery anomalies underwent a coronary CT angiography on a wide detector single-source CT equipment. Fifteen different acquisition patterns were used to trigger the acquisition at the best theoretical moment within the cardiac cycle. The appropriate pattern was automatically selected based on the patient's heart rate and heart rate variability, derived from the patient's ECG. Two independent radiologists qualitatively evaluated images. Results: All acquisitions fully answered the clinical question for a mean effective dose of 0.97±0.34 mSv. Image quality qualified as good or excellent in 94% of cases (47/50). No examination was considered as not assessable but 6% (3/50) were scored as adequate for diagnosis. For these 3 patients, motion artifacts were the main cause of average image quality. No significant visual differences were reported between the different coronary arteries (mean score of 3.6 on a 4-point scale). No correlation between image quality and cardiac parameters were reported ( r =−0.19 and r =0.00, respectively for heart rate and heart rate variability). Conclusions: Personalized multiphasic coronary CT angiography acquisitions could be performed with diagnostic quality for a dose equivalent of <4 months of natural background irradiation. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique identifier: NCT03194763.